REVIEW PAPER BIOTECHNOLOGICAL METHODS AND LIMITATIONS OF MICROPROPAGATION IN PAPAYA (CARICA PAPAYA L.) PRODUCTION: A REVIEW - Baker Al-Shara; Rosna Mat Taha; Kamaludin Rashid (Journal of Animal and Plant Sciences, 2018)
Carica papaya L. is considered one of the most important fruit, especially in tropical and subtropical regions. It generates flowers continuously throughout the year and has been conventionally cultivated by seeds. This review summarizes the morphological and evolutionary descriptions of Carica papaya L., the protocols used to achieve in vitro micropropagation of Carica papaya using different plant tissue culture techniques, as well as the problems faced by papaya micropropagation. While there are many problems encountered during in vitro propagation of papaya through somatic embryogenesis, this review focuses specifically on contamination, rooting processes and acclimatization. Solving these problems will enable a reproducible protocol to be established. Subsequently, high-quality papaya plants can be produced and strains that are resistant towards various diseases can be generated via molecular studies. Cryopreservation and synthetic seeds technology are also potential methods for large scale production and crop improvement of papaya. Keyword: Papaya, Somatic embryogenesis, Acclimatization, Cryopreservation, Synthetic seeds. papaya varieties spread out in Africa and Australia
Keywords: NA